The Effect of Work Placement and Motivation On Employee Performance at Perum Bulog, Pematang Siantar Branch - Muhammad Elfi Azhar; Asri Fatimah (AIBPM Publisher, 2022)
The method in this study using a quantitative approach, the number of samples in this study were 40 respondents based on the results of calculations using the Slovin formula. Data collection techniques in this study using questionnaires or questionnaires distributed to employees of the Bulog Office of Pematang Siantar Branch. The data analysis technique used multiple linear regression, classical assumption test, t test, f test and coefficient of determination. Based on the results of the study, it shows that work placement partially has no effect on the performance of the employees of the Bulog Office of Pematang Siantar Branch with a significant value (0.141) smaller than 0.05 and tcount (1,503) smaller than ttable (1,685), and the test results show motivation partially significant effect on the performance of the employees of the Bulog Office of Pematang Siantar Branch with a significant value (0.001) smaller than 0.05 and tcount (3.776) greater than ttable (1.685) and work placement and motivation simultaneously have a significant effect on the performance of office employees Bulog Branch Pematang Siantar with a value of Fcount = 11,366 which is greater than Ftable 3,252 (seen from Ftable) with a probability value of sig 0.000 less than 0.05.Keywords: Work Placement, Employee Motivation and Performance